Constitutive Activation of NIK Impairs the Self‐Renewal of Hematopoietic Stem/Progenitor Cells and Induces Bone Marrow Failure. (2nd November 2016) - Xiu, Yan; Xue, Wingel Y.; Lambertz, Allyn; Leidinger, Mariah; Gibson‐Corley, Katherine; Zhao, Chen
Abstract : Previously we have shown that loss of non‐canonical NF‐κB signaling impairs self‐renewal of hematopoietic stem/progenitor cells (HSPCs). This prompted us to investigate whether persistent activation of the non‐canonical NF‐κB signaling will have supportive effects on HSPC self‐renewal. NF‐κB‐inducing kinase (NIK) is an important kinase that mainly activates the non‐canonical pathway through directly phosphorylating IKKα. In contrast to our expectations, constitutive activation of NIK in the hematopoietic system leads to bone marrow (BM) failure and postnatal lethality due to intrinsic impairment of HSPC self‐renewal and extrinsic disruption of BM microenvironment through enhancing osteoclastogenesis. The impaired HSPC function is associated with reduced cell proliferation and increased apoptosis and inflammatory cytokine responses. RNAseq analysis of control and NIK‐activated HSPCs reveals that these effects are through non‐canonical NF‐κB signaling without significant changes in the canonical pathway. Gene set expression analysis of RNAseq data reveals globally decreased stem cell signature, increased maturation signature, and increased inflammatory responses. Many genes ( Mpl, Tifab, Emcn, Flt3, Bcl2, and others) that regulate HSPC self‐renewal, lineage commitment, and apoptosis are significantly downregulated—and those genes that regulate inflammatory responses and cell cycle inhibition ( Cdkn2a and Cdkn 2b) are significantly upregulated—by activation of NIK. Importantly, our data demonstrate that activation of NIK‐non‐canonical signaling has distinct phenotypes—smaller spleen size, decreased white blood cell counts, and reduced HSPC proliferation—compared to activation of canonical signaling. Collectively, these data indicate that the balanced non‐canonical NF‐κB signaling is essential for maintaining normal hematopoiesis and NIK‐non‐canonical signaling contributes to the development of BM failure. Stem Cells 2017;35:777–786 Abstract : Constitutive activation of NIK impairs HSPC self‐renewal. Constitutive activation of NIK in the hematopoietic system intrinsically impairs HSPC self‐renewal, reduces HSPC proliferation and increases apoptosis and inflammatory cytokines through NF‐κB non‐canonical signaling. The elevated inflammatory cytokines further damage HSPC self‐renewal. In addition, activation of NIK enhances osteoclastogenesis suggesting a mechanism for extrinsic disruption of bone marrow microenvironment.